The Potential of Carbon Nanoparticles as a Stimulant to Improve the Propagation of Native Boreal Forest Species: A Mini-Review - Sobze, Jean-Marie; Galagedara, Lakshman; Cheema, Mumtaz; Thomas, Raymond; Inoue, Sahari (Frontiers in Forests and Global Change, 2022)
Boreal forests across Canada and other geographic areas globally have vast networks or densities of seismic lines, pipelines, access roads, utility corridors, and multipurpose trails collectively termed “linear disturbances” or “linear features”. Additionally, large areas of disturbances attributed to resource harvesting represent a major anthropogenic impact on the global boreal forest ecosystem. Restoration of these disturbed areas is currently a significant component of global boreal forest management strategies. A key to successful restoration or re-vegetation of these disturbed sites is the availability of highly adaptive native planting materials to grow and establish on the disturbed sites, particularly in varying abiotic stressors or severe environmental conditions. Abiotic stress includes non-living environmental factors, including salinity, drought, waterlogging, or extreme temperatures, adversely affecting plant growth, development, and establishment on field sites. Herein, we present the concept of nanopriming native boreal seeds with microgram concentrations of carbon nanoparticles (CNPs) as an effective approach to improve the propagation and vigor of native boreal forest species. Priming refers to the technique of hydrating seeds in solutions or in combination with a solid matrix to enhance the rate at which they germinate and their germination uniformity. Seed priming has been shown to increase seed vigor in many plant species. In this mini-review, we will provide a brief overview of the effect of nanopriming on seed germination and seed vigor in agricultural plants and native boreal forest species, indicating the potential future applications of CNPs on native boreal species for use in forest reclamation or restoration.